INVESTIGATION OF THE FAT MASS AND OBESITY-ASSOCIATED (FTO) GENE IN PRESCHOOL CHILDREN - Şeref Buğra Tunçer; Duygu Gürleyik; H. Melis Yavuz; İbrahim Acar (Sabiad)
Objective: Obesity is a complex disease defined as being overweight. Previous studies have highlighted familial, environmental, and genetic factors as effective predictors of high body mass index (BMI) and obesity in the preschool period. These studies particularly emphasized that habits acquired in the preschool years affect BMI and obesity. In this populationbased case-control study, it was aimed to reveal for the first time the relationship between fat mass and obesity-related (FTO) gene expression and BMI and obesity in preschool children aged 2-6 living in Turkey. Materials and Methods: Buccal mucosal swabs were collected from 54 preschool children from 3 kindergartens located in Istanbul, Turkey. In the study, the FTO gene expression level in a total of 54 (n=25 girls and n=29 boys) children who were obese (n=14) and non-obese (n=40) according to the International BMI index was determined by the ‘Quantitative Polymerase Chain Reaction’ (qPCR) technique. Result: A correlation was found between FTO gene expression and BMI and obesity in obese and non-obese children with a Mann-Whitney U test (p=0.005). Conclusion: Additional research is needed to better understand the function and prevalence of the FTO gene mutations by performing sequencing analysis of the gene simultaneously in preschool children in Turkey.